2018
DOI: 10.1097/md.0000000000009582
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density after treatment for gastric cancer

Abstract: Changes in bone metabolism among gastric cancer survivors have long been recognized. The aim of our study was to clarify the changes of bone mineral density (BMD) among gastric cancer survivors who underwent endoscopic resection or gastrectomy. Forty-nine patients diagnosed with tumor, node, and metastasis (TNM) stage 1 gastric cancer with pathologic confirmation, who underwent BMD measurement just before the procedure, and had no prior osteoporosis treatment, were studied. BMD was measured with dual energy x-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…According to most but not all studies [ 192 , 193 ], gastric cancer survivors who underwent gastrectomy, compared to the general population [ 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ] or age- and sex-matched healthy controls [ 205 , 206 , 207 , 208 ], have significantly lower BMD, higher prevalence of osteopenia/OP (38.3% [ 196 ] to 55% [ 203 ]) and higher fracture rates (approximately 40% [ 196 , 200 , 205 ]). Bone loss (although of a lesser degree) was also reported in gastric cancer survivors after endoscopic tumor resection undertaken in early stage [ 202 ]. In South Korea, nationwide cohort study of cancer survivors who underwent gastrectomy ( n = 133,179 matched to non-cancer controls, 1:1) demonstrated an increased risk of fractures (HR 1.61; 95% CI 1.53–1.70), which was higher in patients after total gastrectomy (HR 2.18; 95% CI 1.96–2.44) and adjuvant chemotherapy (HR 2.01; 95% CI 1.81–2.23); the elevated OF risk was significantly associated with anemia [ 208 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to most but not all studies [ 192 , 193 ], gastric cancer survivors who underwent gastrectomy, compared to the general population [ 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 ] or age- and sex-matched healthy controls [ 205 , 206 , 207 , 208 ], have significantly lower BMD, higher prevalence of osteopenia/OP (38.3% [ 196 ] to 55% [ 203 ]) and higher fracture rates (approximately 40% [ 196 , 200 , 205 ]). Bone loss (although of a lesser degree) was also reported in gastric cancer survivors after endoscopic tumor resection undertaken in early stage [ 202 ]. In South Korea, nationwide cohort study of cancer survivors who underwent gastrectomy ( n = 133,179 matched to non-cancer controls, 1:1) demonstrated an increased risk of fractures (HR 1.61; 95% CI 1.53–1.70), which was higher in patients after total gastrectomy (HR 2.18; 95% CI 1.96–2.44) and adjuvant chemotherapy (HR 2.01; 95% CI 1.81–2.23); the elevated OF risk was significantly associated with anemia [ 208 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…The causes of OP and subsequent fractures in patients with gastric cancer are multifactorial. Malabsorption (especially of calcium, phosphate, iron, proteins, vitamins B12 and D), malnutrition, weight loss, use of certain medications (e.g., fluorouracil and cisplatin which induce apoptosis of osteoblasts and increase osteoclast activity [ 215 , 216 , 217 ], hormones, radiotherapy, comorbidities, physical inactivity, old age and smoking–all were documented as factors contributing to bone loss and OFs in gastric cancer patients [ 198 , 200 , 202 , 203 , 214 , 217 , 218 ].…”
Section: Hpi-induced Upper Gut Diseases and Osteoporotic Fracturesmentioning
confidence: 99%
“…[11,12] Recently, its serum levels were correlated with bone metabolism and BMD. [13][14][15][16][17] Our study investigated this correlation in adults aged 20 to 59 years and found a negative correlation between serum ALP levels and pelvic BMD, which persisted after adjusting for confounders (Table 2). Females exhibited a more significant negative correlation between serum ALP levels and pelvic BMD than that exhibited by males.…”
Section: Discussionmentioning
confidence: 81%
“…With the increasing number of long-term survivors after gastrectomy, there has been increasing interest in the clinical management of post-gastrectomy syndromes and their possible complications. Among these complications, several reports indicated that patients with gastric cancer, and particularly gastric cancer survivors who underwent gastrectomy, have an increased risk of osteoporosis and fragility fractures [ 153 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 ]. This is in keeping with previous observations in patients with gastrectomy for peptic ulcer disease [ 169 ].…”
Section: Gastric Disordersmentioning
confidence: 99%
“…Despite some studies suggesting an increased risk of osteoporosis after total gastrectomy than partial gastrectomy [ 170 ], or Roux-en-Y than Billroth-I reconstruction [ 171 ], it remains unclear which surgical procedure for gastric cancer confers a greater risk to bone health. Indeed, a certain degree of bone loss has also been described in a restricted cohort of gastric cancer survivors with early stage gastric cancer after endoscopic tumor resection [ 162 ]. In addition to osteoporosis and fractures, calcium malabsorption, together with an increased risk of osteomalacia, has also been described after gastrectomy [ 157 , 172 ].…”
Section: Gastric Disordersmentioning
confidence: 99%